Followership behaviors and barriers to wealth creation. Issue 3 (13th April 2015) - Hayes, Linda A.; Caldwell, Cam; Licona, Bryan; Meyer, Thomas E.
Abstract : Purpose: – The purpose of this paper is to further research in the leader-follower relationship by focussing on followership. Given the need to increase organizational collaboration and cooperation, this research identifies the nature of follower buy-in behaviors and characteristics and develops a continuum of increasing follower compliance to stewardship with the organization. Design/methodology/approach: – This research integrates the insights of highly regarded researchers into a continuum of follower compliance to stewardship and proposes 12 propositions of leaders and followers that address the importance of creating an environment for improved collaboration and cooperation which ultimately leads to increased organizational competitiveness and profitability. Findings: – A continuum of increasing follower buy-in is proposed with the first four zones drawn from past literature (indifference, acceptance, trust, and commitment) and a fifth zone, follower stewardship, being introduced in the paper. The authors argue that understanding and fostering follower behaviors along the continuum improves organizational effectiveness. Research limitations/implications: – This research offers a framework of follower behaviors and characteristics and proposes 12 hypotheses of leaders and followers to improve competitiveness and profitability that can be tested in future research. Practical implications: – This paper provides valuable insights to scholars and practitioners by creating a framework of follower buy-in behaviors and characteristics that will allow leaders to increase the effectiveness of organizational culture, practices, and procedures. The research proposes 12 hypotheses of leaders and followers that can be tested for improving organizational competitiveness and profitability. Social implications: – The paper identifies barriers to creating followership including under-investing in human capital, treating followers as means rather than as ends, thinking short-term, breaking commitments, and so on. Originality/value: – The research develops a solid theoretical background for categorizing and measuring follower buy-in to organizations and introduces follower stewardship to management research.